ANALISIS TERAPI METFORMIN DENGAN GLIMEPIRID PADA PASIEN DIABETES MELITUS TIPE II - Syilfia Hasti; Famella Yustika Rizki; Novia Sinata; Selin Faysa Satiya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Hyperglycemia is a medical condition in the form of an increase in blood glucose levels that exceeds normal. Based on the cause, DM can be classified into 4 groups, namely type I DM, type II DM, gestational DM and other types of DM. The purpose of this study was to determine the comparison of the decrease in blood glucose levels when type 2 DM patients were hospitalized with Metformin and Glimepirid. This research is an observational study with the type of analytic descriptive study. The sample in the study amounted to 103 patients, the sample was taken using a purposive sampling technique and the instrument used was medical record data of type 2 diabetes mellitus patients. Data analysis used the Mann Whitney test and the Wilcoxon test. The results showed that there was no significant difference (p0.05) between generic metformin monotherapy and generic glimepiride monotherapy in lowering transient blood glucose levels.Keywords: Diabetes Melitus Type II, Metformin, Glimepirid, Current Blood Glucose.